SUPERVISION OF INSURANCE ACTIVITIES OF ENTERPRISES - Nosirov Jasur (Scholar Express Journals, 2024)
There is a general agreement that insurance supervision is a fundamental requirement for the sound development of insurance activities. The principle of State intervention has been adopted in almost all countries but it would not be realistic to expect a general agreement on the methods or extent of State intervention.
Keywords: State intervention; insurance supervision